Doppler ultrasound findings in healthy wrists and finger joints before and after use of two different contrast agents. Issue 6 (16th May 2005) - Terslev, L; Torp-Pedersen, S; Bang, N; Koenig, M J; Nielsen, M B; Bliddal, H
Abstract : Objective: To examine the effect of contrast agents on Doppler ultrasound findings in the synovial membrane in the wrist and fingers of healthy volunteers. Material and methods: Eleven healthy subjects were included in the study (5 women and 6 men, mean age 38 years, range (20–60)). They had no clinical signs of inflammatory or degenerative joint diseases. A total of 66 joints were examined—6 joints for each subject: wrist and metacarpophalangeal (MCP) joints 1–5—before contrast injection and after Levovist and SonoVue injection with a 30 minute interval. Results: Colour Doppler activity was detected in 10/55 (18%) MCP joints before contrast injection and in 29/55 (53%) and 28/55 (51%) joints after Levovist (p<0.0001) and SonoVue injection (p = 0.0001), respectively. A significant increase in Doppler activity in the radial (p<0.05) and ulnar (p = 0.01) parts of the wrist joint was detected only after SonoVue injections. With spectral Doppler no difference was found in the resistive index (RI) in the vessels measured before as compared with those only detected after contrast injection. Conclusion: The number of joints with colour Doppler activity in healthy volunteers was increased by the use of contrast agents. No changes in RI were detected. The value of contrast agents remains to be demonstrated in inflammatory diagnostics.